ANNOTATED TRANSLATION FROM THE BOOK TITLED “SHEPHERDING A CHILD’S HEART” - Ricky Perdana (Universitas Gunadarma, 2022)
This research is taken from the book titled Shepherding a child’s heart” written by Tedd Tripp, in which the book clarified parenting. This study collected several problems in the process of translating the text from English into Indonesian. Theresearch is using an introspective and a retrospective method. The data is the annotation of 30 data which consisted of 5 Data For Lexicon, 5 Data For Grammatical Structures, 5 Data for Communication Situation, and 5 Data for Cultural Context.